Visual search, anticipation and expertise in soccer goalkeepers - Savelsbergh, G. J.; Williams, A. M.; van der Kamp, J.; Ward, P. (Journal of Sports Sciences, 2002)
We used a novel methodological approach to examine skill-based differences in anticipation and visual search behaviour during the penalty kick in soccer. Expert and novice goalkeepers were required to move a joystick in response to penalty kicks presented on film. The proportion of penalties saved was assessed, as well as the frequency and time of initiation of joystick corrections. Visual search behaviour was examined using an eye movement registration system. Expert goalkeepers were generally more accurate in predicting the direction of the penalty kick, waited longer before initiating a response and made fewer corrective movements with the joystick. The expert goalkeepers used a more efficient search strategy involving fewer fixations of longer duration to less disparate areas of the display. The novices spent longer fixating on the trunk, arms and hips, whereas the experts found the kicking leg, non-kicking leg and ball areas to be more informative, particularly as the moment of foot-ball contact approached. No differences in visual search behaviour were observed between successful and unsuccessful penalties. The results have implications for improving anticipation skill at penalty kicks.